2002
DOI: 10.1080/09553000210126466
|View full text |Cite
|
Sign up to set email alerts
|

In vitro radiosensitivity measured in lymphocytes and fibroblasts by colony formation and comet assay: comparison with clinical acute reactions to radiotherapy in breast cancer patients

Abstract: In this cohort of patients, a significant correlation between the in vitro results of the comet assay in lymphocytes and clinical acute reactions was detected. The results of the comet assay and of fibroblast colony formation did not correlate with in vitro radiosensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Others confirmed the lack of correlation between cellular radiosensitivity and early skin reactions (32 -34). However, a number of authors have confirmed the correlation between cellular radiosensitivity and late effects (24,25,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Others confirmed the lack of correlation between cellular radiosensitivity and early skin reactions (32 -34). However, a number of authors have confirmed the correlation between cellular radiosensitivity and late effects (24,25,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…However, significant interindividual variation made the test not clinically useful. Oppitz et al (14), using comet assays of lymphocytes of 32 breast cancer patients who underwent irradiation after breast conservation, found that there was a significant correlation (p < 0.05) with acute radiation reactions. Borgmann et al (15), studying late RT effects in 16 pair wise-matched head-and-neck cancer patients 2 to 7 years after curative therapy, found-after in vitro irradiation of lymphocytes-that there was a significant difference in chromosomal damage between patients with severe reactions and patients with mild reactions (7.2 AE 0.8 vs. 5.0 AE 0.3 lethal aberrations).…”
Section: Introductionmentioning
confidence: 97%
“…There was only one study reporting on a positive correlation between individual sensitivity and the extent of acute reaction (Oppitz et al 2001). This result, however, was not confirmed in a recent paper from the same group (Oppitz et al 2002). Almost all these studies were performed with breast cancer patients and the individual sensitivity was generally determined with fibroblasts using the colony assay.…”
Section: Introductionmentioning
confidence: 66%